Clinical comparison of the pneumatic and the combined lithotripters in percutaneous nephrolithotomy. Issue 2 (14th April 2013) - Koc, Gokhan; Akbay, Kaan Esat; Tarhan, Huseyin; Cakmak, Ozgur; Yilmaz, Yuksel
<x xml:space="preserve">Abstract</x> Aim To compare the effectiveness of the pneumatic lithotripter and the combined lithotripter (pneumatic + ultrasonic) in percutaneous nephrolithotomy (PNL). Patients and Methods A total of 150 patients who underwent PNL between March 2009 and January 2011 were included in the study. In the first 49 cases, only the pneumatic lithotripter (group 1) was used, while in the next 101 patients, combined lithotripter (group 2) was used. Differences with regard to total clearance time, fluoroscopic screening time (FST), duration of hospital stay, duration of nephrostomy removal, haematocrit loss, blood transfusion rate and successful treatment rate were investigated between the two groups. Results The general characteristics of the patients were similar between the two groups. However, the mean stone size was statistically significantly higher in group 2. No statistically‐significant difference was detected between the two groups in terms of hospital stay, nephrostomy removal days, successful treatment rate and blood transfusion rate, but compared to group 1 patients, total clearance time, FST and haematocrit loss were significantly less in group 2. Conclusion Although pneumatic and ultrasonic lithotripters are both sufficiently effective when used separately, the combined device was observed to positively influence total clearance time, FST and haematocrit loss significantly.